Hubungan Dukungan Suami dengan Keikutsertaan Ibu Akseptor KB IUD Di Puskesmas Mandiangin Kec. MKS Di Kota Bukittinggi Tahun 2019 - Media Fitri; Cindy Amalia Putri (Jurnal Riset Hesti Medan, 2020)
Family planning (KB) is an action that helps husband and wife to avoid unwanted pregnancies, get a very desirable birth, adjust the pregnancy interval, and control the time of birth in relation to the age of the husband and wife and find the number of children in the family. Pregnancy control in the family planning program is carried out using contraceptives so that the husband's support is needed. The purpose of this study is to see the relationship between husband's support and the participation of IUD family planning acceptors at Puskesmas Mandiangin, MKS Bukittinggi District, 2019. This research was conducted in July 2019. Research methodology analytic survey with Cross Sectional design. The population was family planning acceptors by taking samples of 69 IUD family planning acceptors. Data processing and analysis were performed by computerization using the Chi Square statistical test at a significance limit of 0.05. The results showed that ρ = .0.013. From this value, it is known that the value of ρ <0.05, which indicates that there is a relationship between husband's support and participation in IUD family planning. This relationship is also supported by the value of the OODs ratio = 0.769, which means that a wife who can get support from the mother will have a chance of 0.769 times to become an IUD KB acceptor. It can be concluded that there is a relationship between husband's support and participation in KB IUD in the Work area of the Mandiangin Puskesmas, MKS District, Bukittinggi City, 2019 with a p-value (0.013 <0.05). It can be suggested that the husband should provide support to his wife in using contraception, both emotional support and in the form of appreciation support, in order to create a happy family.